Specific adsorption from an ionic liquid: impedance study of iodide ion adsorption from a pure halide ionic liquid at bismuth single crystal planes. (1st September 2017) - Oll, Ove; Siimenson, Carolin; Lust, Karmen; Gorbatovski, Georg; Lust, Enn
Graphical abstract: Highlights: The CV and EIS characteristics of the Bi( hkl )∣PMImI systems have been studied. Cdl vs. E curves can be considered to be composed of two distinct potential regions. Similarities between ionic liquid and aqueous solution environment are demonstrated. Potential dependent reactive properties of Bi( hkl ) planes are compared. Abstract: Electrical double layer (EDL) formation and adsorption of ions from ionic liquids is important for the fundamental understanding of interfacial processes and their dependence on both the electronic and ionic surface structure. Electrochemical impedance spectroscopy coupled with electrical equivalent circuit modelling has been applied to analyse the interfacial processes that govern the interface between three single-crystal bismuth electrodes with a pure iodide ionic liquid. Major differences in the double layer capacitance are observed for the three bismuth planes in the region of iodide specific adsorption, dependent on both the electronic structure and metallic characteristics of the electrode interface, also observed in case of aqueous iodide solutions. It is shown that this is due to the strong influence of both the electrode material and specifically adsorbed ion layer on the capacitive behaviour, rather than the bulk electrolyte composition. These results suggest a new way of describing the EDL in ionic liquids as well as show how the reactivity of the interface is determined.